2021
DOI: 10.1002/vnl.21830
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion state and hyperelastic behavior of tire tread compounds reinforced with nanoclay: Uniaxial tensile and compression studies

Abstract: Tire‐tread compounds based on natural rubber, butadiene rubber, and styrene‐butadiene rubber (65/20/15) were reinforced with Cloisite 15A. Clay state‐of‐dispersion in the ternary matrix (clay aspect ratio and clay/matrix interface yield strength) was estimated using Halpin–Tsai, Guth, and Leidner–Woodhams–Pukanszky micro‐mechanical models. The aspect ratio suggested by Halpin–Tsai (9.7) and Guth (16) models both propounded partially intercalated microstructure. Transmission electron microscopy micrographs indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[25][26][27][28] Marlow model characterizes the hyperelastic mechanical behavior of unvulcanized rubber, and the Prony series characterizes the relaxation characteristics of unvulcanized rubber. [29][30][31]…”
Section: Constitutive Modeling Of Unvulcanized Rubbermentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28] Marlow model characterizes the hyperelastic mechanical behavior of unvulcanized rubber, and the Prony series characterizes the relaxation characteristics of unvulcanized rubber. [29][30][31]…”
Section: Constitutive Modeling Of Unvulcanized Rubbermentioning
confidence: 99%
“…During the shaping process, unvulcanized rubber shows obvious hyperelastic and viscoelastic mechanical behavior 25–28 . Marlow model characterizes the hyperelastic mechanical behavior of unvulcanized rubber, and the Prony series characterizes the relaxation characteristics of unvulcanized rubber 29–31 …”
Section: Finite Element Modelingmentioning
confidence: 99%
“…In recent years, carbon fiber-reinforced polymer composites have been widely used in aerospace and vehicle industries. [1][2][3][4][5] With the development of high-performance composites, the application of aircraft structures has been developed from secondary load-bearing structures to primary ones, such as wing fixed leading edges, ribs, clips, and angled profiles in parts of Airbus and Boeing commercial aircraft. 6 Due to the service environment, low-velocity impact (LVI) damage is inevitable for thin composite laminated structures.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional ZnO, the modified ZnO led to faster crosslinking and better mechanical properties for the SBR/BR‐based composites. Moreover, to gain a better understanding of filler–polymer interaction, various micromechanical molds were used by Shokoohi 38 to evaluate the impact of nanoclay's characteristics on its dispersion in the ternary blends of SBR/BR/NR. It has been found that the fillers play a crucial role in the improvement of mechanical and thermal properties of rubbery blends because of the nanoclay's specific structure.…”
Section: Introductionmentioning
confidence: 99%